2010
DOI: 10.1073/pnas.1000598107
|View full text |Cite
|
Sign up to set email alerts
|

Steady-state cross-presentation of OVA is mannose receptor-dependent but inhibitable by collagen fragments

Abstract: Cross-presentation allows dendritic cells (DCs) to load antigenic peptides on MHC-I molecules, which is important for activating cytotoxic T cells (CTL) that combat tumors and viruses. We recently showed that, under steady-state conditions, antigens internalized by DCs through the Mannose Receptor (MR) are efficiently cross-presented (1). The MR conveyed antigen into early endosomes, where peptide was loaded on MHC-I (2, 3). Recently, Segura et al. (4) reported that MR-mediated endocytosis is involved in cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
25
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 5 publications
3
25
1
Order By: Relevance
“…5B). It has been suggested that collagenase digestion routinely used to isolate DCs from tissues may not be compatible with MR detection [22]; however, in our hands, both DC populations were also MR-negative when prepared without collagenase digestion (data not shown). Antigen endocytosed via CD205 (also known as DEC-205) enters the MHC class I and MHC class II antigen presentation pathways and is subsequently presented to both CD8 1 and CD4 1 T cells with high efficiency [23].…”
contrasting
confidence: 38%
“…5B). It has been suggested that collagenase digestion routinely used to isolate DCs from tissues may not be compatible with MR detection [22]; however, in our hands, both DC populations were also MR-negative when prepared without collagenase digestion (data not shown). Antigen endocytosed via CD205 (also known as DEC-205) enters the MHC class I and MHC class II antigen presentation pathways and is subsequently presented to both CD8 1 and CD4 1 T cells with high efficiency [23].…”
contrasting
confidence: 38%
“…In a previous study, we reported the isolation of MR-expressing CD11c + splenocytes that were able to cross-present MR-internalized antigens (26). In contrast, work from other groups pointed out that CD8 + DCs, which are the physiologically relevant cross-presenting cells of the spleen under homeostatic conditions, did not express the MR (27).…”
Section: Resultsmentioning
confidence: 92%
“…49 Hence, to test whether IRAP influences MMR functionality, the kinetics of DQ-OVA uptake and degradation by wt versus IRAP -/-macrophages was assessed using flow cytometry. However, no differences between both macrophage types could be observed (Figure 9).…”
Section: Irap-deficiency Does Not Alter Macrophage Mannose Receptor (mentioning
confidence: 99%